THE U.S.COUNTER TERRORISM POLICY. CASE STUDY: THE ROLES OF UNITED STATES DEPARTMENT HOMELAND SECURITY - Ferryan Nugraha (HI 16 UMY 069, 2016)
*69 The threat of terrorism has steadily increased over the last 30 years. With advancement of technology, terrorist acts have become much more destructive and the perpetrators of that act are more elusive. The existence of terrorism as a form of non-traditional threats became more popular as an international issue since the blasting tragedy of the World Trade Centre (WTC) New York on September 11, 2001. The evidence of the WTC tragedy of 11 September 2001 showed that all owned by Americans until that point, can not guarantee the safety of residents of the US. If in the the cold war era, security threat comes from the state, security threats now come in every respect. Terrorists become an epicenter of security discussions the United States in the era after the 9/11 attacks. The threat is now different and requires the United States to make the transformation in response to changes in the threat posed by non-state actors such as terrorists who have caused the deaths of 3,000 casualties in attacks carried out during the day. Therefore, the US government is really trying to find a solution so that the security of the State American really can be guaranteed. It lead the US government take a big step to protect its citizen by establishing a new department that prioritizing national security as a national interest. This institution deliberately formed as an effort to improve security in the country, especially the US public life. Using the political system theory and counter terrorism concept, the author tried to analytically describe a new department established by the United States to deal with the issue of terrorism which is getting stronger especially after the 9/11 case , namely the United State Department of Homeland Security. Keywords: Terrorism, Non-traditional threat, 9/11 Case, National Interest, United State Department of Homeland Security, Political System Theory, Counter-Terrorism.